Dorsal simultanagnosia: An impairment of visual processing or visual awareness? - Jackson, G; Shepherd, T; Mueller, S; Husain, M; Jackson, SR (2006)
When presented with two objects patients with simultanagnosia show a marked impairment at naming both items. This has led many authors to conclude that the second item is not being processed (e.g., Robinson, 2003). However, this deficit may instead reflect a deficit with explicit, or conscious report. We investigated this issue using a semantic priming paradigm that allowed us to assess implicit processing of the second "unseen" item. We presented a patient, with bilateral parietal damage, with pairs of pictures that were either from the same or a different semantic category. The patient was asked to either classify one of the pictures or to name both pictures. When the items were from different categories the patient's classification performance was significantly poorer than when they were from the same category, even though he could rarely explicitly report both items. These findings are consistent with the notion that the meaning of the "unseen" item influenced the reporting of the "seen" item. Consequently, the deficit seen in this patient does not seem to reflect an inability to process more than one item simultaneously but rather a deficit in explicitly identifying multiple items.